Do Lenders Make Less-Informed Investments in High-Growth Housing Markets? - Chen, Sophia (IMF Working Papers; Working Paper ;, 2021)
Nonlocal mortgage lenders with greater exposure to high-growth housing markets accept fewer loan applications in these markets and experience greater stock return volatility. When these lenders expand to high-growth markets, they also ration credit to a significantly greater degree than when they ex-pand to other markets. Mean-variance analyses show that nonlocal lenders' exposure to high-growth markets is associated with more risk, more efficiency, and more return on mortgage portfolios. Overall, these results imply that expansion to high-growth markets leads to a decline in screening and riskier investment by nonlocal lenders, which may reflect a risk-return tradeoff in their portfolio strategy.